2010
DOI: 10.1242/jcs.063859
|View full text |Cite
|
Sign up to set email alerts
|

CHAP is a newly identified Z-disc protein essential for heart and skeletal muscle function

Abstract: SummaryIn recent years, the perception of Z-disc function has changed from a passive anchor for myofilaments that allows transmission of force, to a dynamic multicomplex structure, capable of sensing and transducing extracellular signals. Here, we describe a new Z-disc protein, which we named CHAP (cytoskeletal heart-enriched actin-associated protein), expressed in differentiating heart and skeletal muscle in vitro and in vivo. Interestingly, in addition to its sarcomeric localization, CHAP was also able to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 45 publications
(51 reference statements)
1
54
0
1
Order By: Relevance
“…That is supported by recent findings that synaptopodin 2 expression precedes α-actinin expression (Linnemann et al 2010). On the other hand, overexpression of CHAP resulted in disorganization of α-actinin (Beqqali et al 2010).…”
Section: Ligand Bindingmentioning
confidence: 95%
See 2 more Smart Citations
“…That is supported by recent findings that synaptopodin 2 expression precedes α-actinin expression (Linnemann et al 2010). On the other hand, overexpression of CHAP resulted in disorganization of α-actinin (Beqqali et al 2010).…”
Section: Ligand Bindingmentioning
confidence: 95%
“…Although synaptopodin 2 stimulates actin polymerization in solution, it is thought that synaptopodin family members work together with specific isoforms of α-actinin in cells to promote actin polymerization (Asanuma et al 2005;Beqqali et al 2010). HEK cells do not contain appreciable α-actinin 4 or synaptopodin and have no stress fibers.…”
Section: Actin Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 The SNP rs10824026 is located on chromosome 10q22, 5-kb upstream of SYNPO2L. 18 Beqqali et al 41 identified the gene as encoding a cytoskeletal protein, which is highly expressed in the Z-disc of cardiac and skeletal muscle. They renamed it CHAP, cytoskeletal heart-enriched actin-associated protein.…”
Section: The 4q25 Locusmentioning
confidence: 99%
“…SYNPO2L and MYOZ1 encode signalling proteins that localise to the Z-disc and modulate cardiac sarcomeric function. 71,72 CAV1 is an important membrane protein, which plays a role in cellular signalling, and has been demonstrated to interact with ion channels, including HCN4 and KCNN3. [73][74][75][76] In addition to the variants identified in the aforementioned GWAS for AF, common variants that have previously been implicated in GWAS for Brugada syndrome have also been demonstrated to influence risk in AF.…”
Section: Common Genetic Variants and Atrial Fibrillation In The Genermentioning
confidence: 99%